Review of baseline studies on energy policies and indicators in Malaysia for future sustainable energy development - Hannan M.A.; Begum R.A.; Abdolrasol M.G.; Hossain Lipu M.S.; Mohamed A.; Rashid M.M. (Elsevier Ltd, 2023)
Benchmarking; Cost effectiveness; Efficiency; Electric power systems; Energy policy; Environmental impact; Environmental protection; Environmental regulations; Fossil fuels; Global warming; Indicators (instruments); Planning; Sustainable development; Baseline studies; Electricity generation; Malaysians; Management and utilization; Production and consumption; Renewable energies; Sustainable energy development; United nations framework convention on climate changes; Energy efficiency